THU0473 IS PAIN INTENSITY ASSOCIATED WITH EARLY MORTALITY IN PATIENTS WITH PSORIATIC ARTHRITIS?. (2nd June 2020) - Vela, J.; Cordtz, R.; Kristensen, S.; Kjær Petersen, K.; Arent-Nielsen, L.; Torp-Pedersen, C. T.; Dreyer, L.
Abstract : Background: Studies regarding excess mortality among patients with psoriatic arthritis (PsA) are conflicting due to the heterogenous nature of the disease. Thus, identifying risk factors for mortality is crucial, but few studies have examined these in PsA. Presence of chronic pain can cause excess mortality and since pain is prevalent among patients with PsA this association should be explored. Objectives: To investigate whether higher cumulative pain intensity is associated with an excess mortality ratio in patients with PsA. Methods: A nested case-control study was performed using data from the national Danish healthcare registers and the DANBIO rheumatology register. Cases were patients who died while followed in routine care. Cases were matched on sex, year of birth and calendar period of DANBIO entry with up to five controls. The main exposure of interest was the mean pain intensity (all causes) reported during the time followed in routine rheumatology practice. The pain intensity was measured on a visual analogue scale (VAS) ranging from 0 (no pain) to 100 (worst imaginable pain). Conditional logistic regression was used to calculate the odds of mortality per 5 unit increase in VAS pain while adjusting for inflammatory markers. Results: The Danbio PsA cohort consisted of 8019 patients. In total, 266 cases, i.e. PsA patients who died during the observational period, were identified and matched with 1198 controls (4.5 controls per case). Increasing pain intensity was associated with increased odds of mortality (OR 1.05, 95%CI 1.01 to 1.09) in the crude model, but the association disappeared when adjusting for age, sex, calendar time, socioeconomic status, average c-reactive protein and swollen joint count during the observation period (OR 0.98, 95%CI 0.93-1.03). Age, average CRP, biological DMARD use, glucocorticoid use, and comorbidities (see table ) increased the odds of mortality. Conclusion: These results indicate that experienced pain in itself is not associated with excess mortality. Age, recent glucocorticoid use, biological DMARD use, chronic pulmonary disease, diabetes, cancer and cardiovascular disease were all associated with an increased mortality. Disclosure of Interests: None declared